Studies on a widely-recognized snail model species (Lymnaea stagnalis) provide further evidence that vertebrate steroids do not have a hormonal role in the reproduction of mollusks - Fodor, István; Schwarz, Tamar; Kiss, Bence; Tapodi, Antal; Schmidt, János; Cousins, Alex R. O.; Katsiadaki, Ioanna; Scott, Alexander P.; Pirger, Zsolt (Frontiers in Endocrinology, 2022)
Experiments were carried out to determine whether, as with other mollusks that have been studied, the snail, Lymnaea stagnalis, can absorb, esterify and store vertebrate steroids that are present in the water. We also carried out experiments to determine whether neural tissues of the snail could be immunohistochemically stained with an antibody to human aromatase (a key enzyme that catalyzes the conversion of testosterone [T] to 17β-estradiol [E2]); and, if so, to determine the significance of such staining. Previous studies on other mollusks have reported such staining and have proposed this as decisive evidence that mollusks have the same steroid synthetic pathway as vertebrates. We found that snails absorb, esterify and retain esterified T, E2, progesterone and ethinyl-estradiol (albeit with an absorption rate about four times slower, on a weight basis, than the mussel, Mytilus edulis). We also found that not only anti-human aromatase, but also anti-human nuclear progesterone receptor (nPR) and anti-human gonadotropin-releasing hormone antibodies immunohistochemically stained snail neural cells. However, further experiments, involving gel electrophoretic separation, followed by immunostaining, of proteins extracted from the neural tissue, found at least two positively-stained bands for each antibody, none of which had masses matching the human proteins to which the antibodies had been raised. The anti-aromatase antibody even stained the 140 kDA ladder protein used as a molecular weight marker on the gels. Mass spectrometric analysis of the bands did not find any peptide sequences that corresponded to the human proteins. Our findings confirm that the presence of vertebrate-like sex steroids in molluscan tissues is not necessarily evidence of endogenous origin. The results also show that immunohistochemical studies using antibodies against human proteins are grossly non-specific and likely to have little or no value in studying steroid synthesis or activity in mollusks. Our conclusions are consistent with the fact that genes for aromatase and nPR have not been found in the genome of the snail or of any other mollusk. .